Loss of SMAD1 in acute myeloid leukemia with KMT2A::AFF1 and KMT2A::MLLT3 fusion genes - Dietsche, Lisa; Stirm, Kristin; Lysenko, Veronika; Schneidawind, Corina; Tzankov, Alexandar; Müller, Anne; Theocharides, Alexandre P. A. (Frontiers in Oncology, 2025)
IntroductionKMT2A-rearrangements define a subclass of acute leukemias characterized by a distinct gene expression signature linked to the dysfunctional oncogenic fusion proteins arising from various chromosomal translocations involving the KMT2A (also known as MLL1) gene. Research on the disease pathomechanism in KMT2A-rearranged acute leukemias has mainly focused on the upregulation of the stemness-related genes of the HOX-family and their co-factor MEIS1.ResultsHere we report the KMT2A::AFF1 and KMT2A::MLLT3 fusion gene-dependent downregulation of SMAD1, a TGF-β signaling axis transcription factor. SMAD1 expression is lost in the majority of AML patient samples and cell lines containing the two fusion genes KMT2A::AFF1 and KMT2A::MLLT3 compared to non-rearranged controls. Loss of SMAD1 expression is inducible by introducing the respective two KMT2A fusion genes into hematopoietic stem and progenitor cells. The loss of SMAD1 correlated with a markedly reduced amount of H3K4me3 levels at the SMAD1 promoter in tested cells with KMT2A::AFF1 and KMT2A::MLLT3. The expression of SMAD1 in cells with KMT2A::AFF1 fusion genes impacted the growth of cells in vitro and influenced engraftment of the KMT2A::AFF1 cell line MV4-11 in vivo. In MV4-11 cells SMAD1 expression caused a downregulation of HOXA9 and MEIS1, which was reinforced by TGF-β stimulation. Moreover, in MV4-11 cells SMAD1 presence sensitized cells for TGF-β mediated G1-arrest.ConclusionOverall, our data contributes to the understanding of the role of TGF-β signaling in acute myeloid leukemia with KMT2A::AFF1 by showing that SMAD1 loss can influence the growth dynamics and contribute to the pathogenic expression of disease driving factors.